The Effect of Work and Personal Life Integration on Employee Performance with Work Stress as an Intervening Variable at the Binjai City Manpower, Industry, and Trade Office - Dermawaty Br. Sihombing; Hernawaty; Erwansyah (Equivalent : Journal of Economic, Accounting and Management, 2026)
The increasing integration of work and personal life in the modern technology-based work environment has presented both opportunities and challenges for employee performance, especially in public sector organizations. While work-life integration offers flexibility, it also has the potential to increase work stress due to the blurring of role boundaries between work and personal life. This study aims to analyze the influence of work-life integration on the performance of employees with work stress as an intervening variable at the Binjai City Manpower, Industry, and Trade Office. This study uses an associative quantitative research design involving 36 civil servants selected through purposive sampling techniques. Data was collected using a structured questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using the SmartPLS 3.3.3 application. The results show that work-life integration has a positive and significant effect on employee performance, which indicates that effective integration can improve productivity, focus, and work quality. In addition, work-life integration also has a positive effect on work stress, suggesting that increased role integration can trigger psychological distress when role boundaries are unclear. Work stress has also been shown to have a positive but relatively small effect on employee performance, which indicates the presence of eustress that can encourage motivation and work alertness. Furthermore, work stress has been shown to partially mediate the relationship between work-life integration and employee performance. These findings confirm that while work-life integration is important in improving employee performance, its implementation needs to be accompanied by an effective stress management strategy to maintain the sustainability of employee welfare and achieve optimal organizational performance in public sector institutions.